Lower Back Pain Prevention Education In The Community In Sidodadi Village, Beringin District - Bintang, Siti Sarah Bintang Sarah; Berampu, Sabirin; Handayani, Dwi; Jannah, Miftahul (JURNAL PENGMAS KESTRA (JPK), 2024)
Low back pain (LBP) is characterized by pain, muscle tension, or stiffness localized below the ribs and above the crease of the buttocks, with or without leg pain. It can be categorized as non-specific LBP, a serious condition, or a radicular syndrome. Classifying LBP as acute (lasting less than 6 weeks), sub-acute (6 to 12 weeks), or chronic (more than 12 weeks) can aid in prognosis and guide management. Predictors of persistent disability from LBP include genetics, symptoms, lifestyle, social and psychological factors, and comorbidities. 7 However, no single risk factor is strongly predictive. The mechanisms of action of these risk factors are still unknown, but sleep disturbances and severe stress, for example, may lead to excessive activation of glial cells and thus to low-grade inflammation, leading to central sensitization, i.e. widespread pain. The implementation of community service activities was carried out through notification via the information platform at the village office with a sample of 15 residents in Sidodi Village, Beringin District. It is recommended that residents maintain their health, especially physically, so that, in addition, it is also recommended to continue to pay attention to or apply a healthy daily lifestyle and maintain their physical condition so that they remain healthy.